2012
DOI: 10.1016/j.media.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 3D MR image-based computer models of pathologic hearts, augmented with histology and optical fluorescence imaging to characterize action potential propagation

Abstract: Cardiac computer models can help us understand and predict the propagation of excitation waves (i.e., action potential, AP) in healthy and pathologic hearts. Our broad aim is to develop accurate 3D MR image-based computer models of electrophysiology in large hearts (translatable to clinical applications) and to validate them experimentally. The specific goals of this paper were to match models with maps of the propagation of optical AP on the epicardial surface using large porcine hearts with scars, estimating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 74 publications
2
19
0
1
Order By: Relevance
“…For the VT-inducible heart, the average predicted VT cycle length was slightly longer (by 23 ms) compared to the recorded cycle length, possibly due to input model parameters assigned to different zones. However, we demonstrated in [13] very good correspondence between our classification and the extent of scars in histological images. Also, in a recent study, we reported good agreement between infarct classifications obtained using contrast-enhanced MRI methods (clinically used) and the DW method.…”
Section: Discussion and Future Worksupporting
confidence: 59%
See 1 more Smart Citation
“…For the VT-inducible heart, the average predicted VT cycle length was slightly longer (by 23 ms) compared to the recorded cycle length, possibly due to input model parameters assigned to different zones. However, we demonstrated in [13] very good correspondence between our classification and the extent of scars in histological images. Also, in a recent study, we reported good agreement between infarct classifications obtained using contrast-enhanced MRI methods (clinically used) and the DW method.…”
Section: Discussion and Future Worksupporting
confidence: 59%
“…Some input values for model parameters were taken from our recent optical imaging ex-vivo study [13] in infarcted swine hearts, and they were assigned by zones. The restitution curves in that study were generated by plotting APD90 (ms) versus cycle length, (CL in ms), at different pacing frequencies (e.g., in the normal zone, measured APD90 = 0.218 × CL +151 and computed APD90 = 0.213 × CL +160).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Studies have been trying to determine the consequences of myocardial infarctions in small (rat [41]) hearts and larger (porcine [43,27]) hearts. In these studies it was shown that acute infarction led to a decrease in regional wall thickness and an increased radius of curvature, mostly in the border zone (BZ) -which is the zone close to the dense scar region but with a more heterogeneous nature due to the persistence of surviving blood vessels that continue to supply oxygen to isolated cells.…”
Section: Infarcts and Their Impact On Heart Fiber Geometrymentioning
confidence: 99%
“…The MR parameters were given in our previous EP studies [12,14], together with the methodology regarding the construction of the 3D model from apparent diffusion coefficient (ADC) maps, which were next used to segment the heart into three zones: healthy tissue, BZ and infarct scar. Surface meshes were then created for each heart from the 3D anatomy MR scan, and volumetric tetrahedral meshes were generated with TetGen package.…”
Section: Construction Of the 3d Mri-based Computer Model Of The Heartmentioning
confidence: 99%
“…For instance, the value in the anisotropy ratio is set to 0.14 for a wave propagating almost 2.7 times as fast along the fiber as in the transverse direction. The input values for model parameters were taken from our recent optical fluorescence imaging study performed in infarct hearts [14], and these values were assigned per zone (i.e., infarct, BZ and healthy) and are given in Table 1. Specifically, the values for a (tuning the duration of AP), k (tuning the up-stroke of AP) and the normalized conductivity d were set as in Table 1 (note that a and k values in the scar zone are similarly set like those for BZ, but are in fact irrelevant because the scar is unexcitable, thus d is to 0 (i.e., the AP wave does not propagate through the scar).…”
Section: Mathematical Modelmentioning
confidence: 99%